Strengthening Character-Based Positive Parenting Patterns for Parents in Depok City - Susanto, Susanto (International Journal of Community Engagement Payungi, 2023)
Various negative phenomena carried out by our children require serious handling with various strategies, including strengthening character education. Therefore, this activity aims to provide theoretical and practical assistance to strengthen character-based positive parenting patterns for parents in Depok City. This activity adopts the Participatory Action Research (PAR) method which involves the participation of participants. Participants in this activity were parents from Cilodong District, Depok City, totaling 115 people. This activity was carried out in the Meeting Hall of the Character Genius Islamic School Elementary School, Depok City. The results of this mentoring show that parents as activity participants are increasingly understanding: 1) their roles and functions in the family environment, namely providing serious and sustainable assistance to children's growth and development, so as not to be eroded by negative factors of technological development; 2) positive parenting for children has 3 positive impacts, namely: making the relationship between parents and children closer; make parent-child communication more effective and increase the child's self-confidence and happiness. The conclusion of this activity has a positive impact on parents because it is given strengthens parenting patterns in the family both theoretically and practically.